The Postcolonial Perverse: Hybridity, Desire, and the Filipino Nation in Federico Licsi Espino, Jr.'s Lumpen. - Garcia, J. Neil C. (Intersections: Gender & Sexuality in Asia & the Pacific, 2006)
The author reflects on the concept and/or practice of hybridity in the Philippines. He discusses the representation of hybridity in the novel Lumpen, by Federico Licsi Espino, Jr. According to the author, the canonical historiographic and literary renderings of the Filipino nation have invariably been presumptively heterosexual and, not surprisingly, nativist.